2018
DOI: 10.21608/bvmj.2018.29409
|View full text |Cite
|
Sign up to set email alerts
|

Survey On Some Hormonal Residues In Chicken Meat, Liver And Kidneys

Abstract: The study was planned to estimate the 17β-Estradiol and Zeranol residues in 100 samples of chicken carcasses and their livers and kidneys. Samples were randomly collected from different localities in Cairo and Giza markets and were analyzed using Enzyme-linked Immuno Sorbent Assay (ELISA) method. The mean values (ppb) of 17β-Estradiol in chicken muscle, livers and kidneys were 0.782±0.07, 1.53±0.09 and 2.077±0.08, respectively. While, the mean values (ppb) of Zeranol in chicken muscle, livers and kidneys were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…While, higher findings were obtained by Xiaoming et al [22] who found zeranol residues (2.5 ppb) in liver samples of chickens. Moreover, lower findings were recorded by Ibrahim et al [19] (0.106 and 0.123 ppb for meat and liver samples, respectively).…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…While, higher findings were obtained by Xiaoming et al [22] who found zeranol residues (2.5 ppb) in liver samples of chickens. Moreover, lower findings were recorded by Ibrahim et al [19] (0.106 and 0.123 ppb for meat and liver samples, respectively).…”
mentioning
confidence: 55%
“…Lower findings were obtained by Doyle [15] who found that 17βestradiol in chicken meat was ranged from < 0.03-0.02 ppb; and Akhmet et al [16] who collected a chicken breast and wing samples from USA, Russia and Ukraine, where estradiol was detected in the mean value of 0.004, 0.001 and 0.002 ppb in wing samples, while was 0.004, 0.001and 0.001 ppb in breast samples, respectively. While, higher findings were obtained by Sadek et al [17] who found 17βestradiol in chicken meat and Liver were 0.865, 4.216 ppb, respectively; Kadim et al [18] (0.704 ppb in chicken meat samples), and Ibrahim et al [19] who recorded detection of 17βestradiol in all of the examined chicken meat samples with mean values of 0.782 and 1.53 ppb, respectively.…”
mentioning
confidence: 72%
“…Zeranol residue was found in many different types of samples such as bovine meat, liver, and kidney of cattle (Mor et al, 2011, Yücel et al, 2018, chicken meat, liver and kidney of chicken (Hemmat et al, 2018), and bovine urine (Matraszek-Zuchowska et al, 2013). Fortunately, zeranol residue is not stable during storage and cooking treatment (Kukhtyn et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the EU, the use of hormones and hormone-like substance swith action to stimulate the growth of farm animals is prohibited according to Council Directive 96/22/EC and their monitoring must to be done according to Council Directive 96/23/EC. Despite the ban on hormones in animal husbandry, there is literature data on their possible use in meat production (Jeong et al, 2010;Matraszek-Zuchowska et al, 2017;Ibrahim et al, 2018). In some countries, Canada, Australia, and the USA, hormones such as oestradiol, testosterone, progesterone, and their esters are authorized.…”
mentioning
confidence: 99%
“…But in recent years, increased research information about the identification of hormones and hormonal growth-promoting agents in animal-originated food. The incidence of hormone residues in such types of food and food products beyond the tolerance acts as a risk factor for the occurrence of potential public health problems (Matraszek-Zuchowska et al, 2017;Ibrahim et al, 2018;Hirpessa et al, 2020).…”
mentioning
confidence: 99%